Climate Change Mitigation: Nepal’s Priority Concern - Lohani, Mohan P. (NCWA Annual Journal, 2025)
The world today is beset with multi-faceted conflicts and numerous challenges threatening international peace, security, social harmony and peaceful co-existence. The crisis, however, unleashed by unprecedented climate change has overshadowed ongoing conflicts with global implications. Several climate conferences, including the latest COP-29 held at Baku, the capital of Azerbaijan in November last year have confirmed the public perception and belief that climate change is no longer the concern of a particular country. It has already become an issue of global concern. There is a growing realization on all sides at home and abroad that Nepal placed in risk zone is highly vulnerable to adverse impact of climate change. Nepal being a mountainous country is deeply concerned about fast melting Himalayan glaciers, the source of clean water and energy. UN Secretary General Antonio Guterres who observed the climate crisis being experienced by Nepal during his visit to this country in October 2023 has added his voice to Nepal’s concern, urging all member states to work together for climate crisis mitigation. Nepal which is not responsible for carbon emission leading to global warming has raised its voice for climate finance and justice.